Cooperative optimal configuration of integrated energy system considering uncertainty factors of source-load. Issue 1 (1st February 2022) - Li, Tong; Sun, Heyang; Shi, Zewen; Li, Qingchun; Zhang, Jian; Huang, Bonan
Abstract: Existing studies have focused on the source-load uncertainty in the integrated energy system (IES), but ignored the impact of the integrated demand response (IDR) uncertainty. Therefore, this paper comprehensively considers the uncertainties of renewable energy, load and IDR, and proposes a two-layer optimal and configuration model. In addition, non-parametric density estimation and Copula theory are combined to improve the traditional source-load uncertainty probability model. Meanwhile, based on the double uncertainty of baseline load and price elasticity coefficient, interval fuzzy calculation method is proposed to modify the elastic coefficient. On this basis, aiming at the minimum annual comprehensive operating cost of the system, the configuration of energy hub equipment was solved in layers. The calculation results show that including IDR in configuration calculation helps to suppress the net load curve of the system, reduce the influence of user energy and intermittent power output uncertainty on system configuration results, and make the system run economically and environmentally.